Searching for Potential HDAC2 Inhibitors: Structure-activity Relationship Studies on Indole-based Hydroxamic Acids as an Anticancer Agent - Shirbhate, Ekta; Divya; Patel, Preeti; K. Patel, Vijay; Veerasamy, Ravichandran; Sharma, Prabodh C.; Rajak, Harish (Letters in Drug Design & Discovery, 2020)
Aim: To predict the most potent indole based HDAC2 inhibitors from several scientific reports through the process of lead identification and SAR development. Background: The current scenario is observing Histone Deacetylase (HDAC) as an alluring molecular target for the designing and development of drugs for cancer treatment. Objective: To identify the lead and establish structure-activity correlation among indole based hydroxamic acid to find out promising HDAC2 based anticancer agent. Methods: A dataset containing 59 molecules was analyzed using structure and ligand-based integrated approach comprising atom-based 3D-QSAR (Quantitative Structure-Activity Relationship) and pharmacophore study, e-pharmacophore mapping and molecular modeling methodologies. The finest model was prepared by amalgamating the properties of electronegativity, polarizability, Vander Waals forces and other conformational aspects. Results: The result of 3D QSAR analysis, performed for 4 PLS factor, provided the following statistical information: R2 = 0.9461, Q2 = 0.7342 and low standard of deviation SD = 0.1744 for hypothesis ADDDH.10 and R2 = 0.9444, Q2= 0.7858 and again low standard of deviation SD = 0.1795 for hypothesis DDHRR.12. The XP molecular docking showed intermolecular interactions of small molecules with amino acids such as GLY154, HIP145, PHE210, HIE183, internal H2O and Zn2+. Conclusion: The interpretation of data generated as a result of this investigation clearly hints about the better biological activity of test compounds as compared to SAHA. Hence, the outcome of these structure and ligand-based integrated studies could be employed for the design of novel arylindole derivatives as a potent HDAC inhibitor.
Keywords: pharmacophore